The Effect of Green Knowledge, Green Awareness, Strategic Orientation, and Government Regulation on Business Sustainability of Culinary MSMEs in Bogor City - Nurul Hidayati; Amberly Anadya Prames; Nisa Zahra; Heti Mulyati; Derry Dardanella; Rika Zahera (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Climate change has become a pressing global concern, including in Indonesia. Bogor City, home to 26,696 culinary MSMEs, faces challenges such as carbon emissions from production processes that disregard environmental considerations. Addressing these challenges requires a more sustainable production approach, one of which is the implementation of green manufacturing. Purpose: This study aimed to analyze the effect of green knowledge, green awareness, strategic orientation, and government regulation on the business sustainability of culinary MSMEs in Bogor City, with green manufacturing as a mediating variable.Methodology: A quantitative approach was employed to assess the perceptions of culinary MSME actors toward the variables of green knowledge, green awareness, strategic orientation, government regulation, green manufacturing, and business sustainability using a questionnaire instrument. A survey was also conducted to identify the factual conditions of MSMEs. The study was carried out from February to June 2025, involving 155 respondents, and was analyzed using SEM-PLS with SmartPLS 4.0.Findings: The results showed that environmental awareness and knowledge, business strategy, and government regulation played significant roles in promoting green manufacturing (GM) and strengthening business sustainability. GM practices included energy efficiency, waste management, and eco-friendly raw materials. The study highlights the importance of synergy between environmental understanding, public policy, and strategic orientation in encouraging culinary MSMEs to adopt greener, more adaptive, and sustainable business practices.Conclusion: Green knowledge, green awareness, and government regulation significantly and positively influenced the implementation of green manufacturing, highlighting the critical role of environmental understanding, awareness, and policy support in promoting eco-friendly production. However, strategic orientation showed no significant effect, as many culinary MSMEs remain focused on short-term goals rather than sustainability-oriented strategies. Although green manufacturing had a positive but insignificant impact on business sustainability, this suggests that while it supports efficiency and competitiveness, it has not yet been fully integrated into MSMEs' core strategies. This occurs because culinary MSME actors in Bogor City are still oriented toward short-term profits to meet their daily operational needs. Therefore, further training, mentoring, and supportive policies are essential to strengthen the connection between green practices and long-term business sustainability.Originality/value (State of the art): This study emphasizes the implementation of green manufacturing within the culinary MSME sector, linking it to green knowledge, green awareness, government regulation, and strategic orientation as determinants of sustainability performance. However, the diversity of practices among these MSMEs indicates varying levels of understanding and only partial implementation of green manufacturing principles. Keywords:     green awareness, green knowledge, green manufacturing, business sustainability, culinary MSMEs